METODE EKSPRESI BEBAS TERHADAP KREATIVITAS MENGGAMBAR SISWA KELAS IV PADA MATA PELAJARAN SENI BUDAYA DI SD NEGERI PASIR AWI KABUPATEN TANGERANG - Ubaidillah; Muhammad Soleh Hapudin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to determine the creativity of drawing students in grade IV through the free expression method in the subject of art and culture at Pasir Awi Elementary School, Tangerang Regency. This study uses a narrative method with a qualitative approach. Determination of research subjects using purposive sampling techniques. Data collection techniques through observation, interviews, and documentation. Data analysis techniques through Miles and Huberman model analysis. The results of the study can be concluded that: (1) the steps of the free expression method on the creativity of drawing students in grade IV by teachers, namely the teacher offers and determines the theme, the teacher determines the choice of tools/materials, the teacher explains the form of drawing activities, the teacher provides motivation and communicates. (2) creativity in drawing through the free expression method in grade IV students of Pasir Awi Elementary School, Tangerang Regency from 35 students, those who have a score of 80-100 are included in the high category, totaling 8 students with a percentage of 23%. Students who have a score of 60-79 are included in the medium category, totaling 17 students with a percentage of 48%. Then students who have a score <60 are included in the low category, totaling 10 students with a percentage of 29%. So it can be concluded that the creativity of drawing of grade IV students through the free expression method is classified as moderate (48%) as many as 17 students out of a total of 35 students.